2014
DOI: 10.1037/a0036988
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory specificity among preschool-aged children.

Abstract: Overgeneral memory refers to difficulty retrieving specific autobiographical memories and is consistently associated with depression and/or trauma. The present study developed a downward extension of the Autobiographical Memory Test (AMT; Williams & Broadbent, 1986) given the need to document normative developmental changes in ability to retrieve specific memories among preschoolers. Confirmatory factor analysis and item response theory demonstrated that the AMT-Preschool Version maintained the same underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 50 publications
9
43
0
Order By: Relevance
“…The current inquiry examined the relations between autobiographical memory, source memory for selfand other-referenced stimuli, and self-knowledge in children. Consistent with previous research, source monitoring ability increased with age across early childhood (Drummey & Newcombe, 2002;Foley & Johnson, 1985;Welch-Ross, 1995b), as did autobiographical memory (Hayne et al, 2011;Nuttall et al, 2014;Tustin & Hayne, 2010), and self-descriptive details (Eder, 1989(Eder, , 1990Harter, 1999;Montmayor & Eisen, 1977). We also found the expected ageinvariant memory advantage for both actions and objects encoded in a self-referent context (see Cunningham et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current inquiry examined the relations between autobiographical memory, source memory for selfand other-referenced stimuli, and self-knowledge in children. Consistent with previous research, source monitoring ability increased with age across early childhood (Drummey & Newcombe, 2002;Foley & Johnson, 1985;Welch-Ross, 1995b), as did autobiographical memory (Hayne et al, 2011;Nuttall et al, 2014;Tustin & Hayne, 2010), and self-descriptive details (Eder, 1989(Eder, , 1990Harter, 1999;Montmayor & Eisen, 1977). We also found the expected ageinvariant memory advantage for both actions and objects encoded in a self-referent context (see Cunningham et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Using mirror selfrecognition to test Howe and colleagues' theory limits the period of qualitative change to the period of 18-24 months. However, amnesia persists beyond infancy, as reflected in the slow growth of memories for events in early childhood (Hayne, Gross, McNamee, Fitzgibbon, & Tustin, 2011;Nuttall, Valentino, Comas, McNeill, & Stey, 2014;Tustin & Hayne, 2010). Howe and colleagues argue that the gradual offset of childhood amnesia is related to gradual development in the self-concept, strengthening the anchor to which memories are attached.…”
mentioning
confidence: 99%
“…The ability to recall specific memories develops as children age (e.g., Nelson, 1990;Nuttall et al, 2014). Our findings suggest that this capacity continues to develop from adolescence into adulthood.…”
Section: Discussionmentioning
confidence: 67%
“…In typically developing children, the ability to report more specific memories increases with age (Nelson & Fivush, 2004;Nuttall, Valentino, Comas, McNeil, & Stey, 2014) presumably due to developmental advances in, for example, language skills, knowledge base, strategy use, and storage capacity (Howe & Courage, 1997). To the extent that memory is still developing during early adolescence (Ogle et al, 2013), teens may evince less specificity, that is, greater rAMS, than adults.…”
Section: Age Differencesmentioning
confidence: 96%
“…There are also written versions of the AMT in which participants are asked to write down their memories to the cue words (Raes, Verstraeten, Bijttebier, Vasey, & Dalgleish, 2010), a pre-school version (the AMT-PV; Nuttall et al, 2014), a constrained version which asks participants to recall memories for events 24 hours post trauma (Nixon, Ball, Sterk, Best, & Betty, 2013, study 1) and a minimal instruction version of the task (Debeer et al, 2009) to name a few. Research with adults has suggested that the original ATM (Williams & Broadbent, 1986) may not be sensitive enough to assess memory specificity in non-clinical samples (Debeer et al, 2009).…”
Section: Ogm Measurementmentioning
confidence: 99%